Financial Statement Analysis to Assess Company Financial Performance - Octavianti Purnama; Vivin Hanitha; Tri Angreni Angreni (eCo-Fin, 2020)
PT Shinrai Indonesia is one type of distributor company engaged in the marketing of products, especially food support materials. Therefore, the purpose of this study is to determine the financial condition and developments occurring within the company, to identify problems or problems in the company's finances by providing inputs and suggestions that can assist in overcoming weaknesses and to support management policies that have been implemented. set together. The research method carried out by the author is library research by taking references from books that are closely related to the subject matter and research objects, both from the library and from other sources. And field research (field research) by collecting data from companies. Based on the results of research on the financial statements of PT Shinrai Indonesia from 2014 – 2018, it can be seen that in 2014 the company had fairly good financial ratios, both for liquidity ratios, activity ratios, profitability and solvency ratios. The conclusion that can be drawn by the author is that the state of the company from 2014 to 2018 has decreased and increased for all ratios used, although there are several ratios that have improved for that year therefore it is necessary to do better handling for the progress of the company. In addition, the profits contained in the company also tend to experience a small increase from 2014 - 2018. Based on these conclusions the authors suggest the company to take various corrective actions, including negotiating with creditors to extend or reschedule payments on debt, increase the level of sales, do more vigorous promotion